A RISC Building Block Set for Structured Parallel Programming - Danelutto, M.; Torquati, M. (2013 21st Euromicro International Conference on Parallel, Distributed, and Network-Based Processing, 2013)
We propose a set of building blocks (RISC-pb2l) suitable to build high-level structured parallel programming frameworks. The set is designed following a RISC approach. RISC-pb2l is architecture independent but the implementation of the different blocks may be specialized to make the best usage of the target architecture peculiarities. A number of optimizations may be designed transforming basic building blocks compositions into more efficient compositions, such that parallel application efficiency may be derived by construction rather than by debugging.